2015
DOI: 10.1007/s40279-015-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Exercise Science: A Commentary on Existing Studies and Suggestions for Future Directions

Abstract: Policies regarding cannabis use are rapidly changing, yet public officials have limited access to scientific information that might inform the creation of these policies. One important area in which to begin investigations is the link between recreational cannabis use and health, specifically exercise. There are common anecdotal reports that cannabis decreases motivation, including motivation to exercise. On the other hand, there are also anecdotal reports that cannabis is used prior to athletic activity. In f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 56 publications
2
26
0
1
Order By: Relevance
“…Prior research has posited that endogenous cannabinoids (i.e., cannabinoids occurring naturally in the body) provide a reward pathway for the addictive properties of PA, which may be disturbed by the consumption of exogenous cannabinoids (i.e., cannabis use), but this mechanism is not fully understood (17). Alternatively, it has been suggested that exogenous cannabinoids have indirect positive effects on health by reducing pain and in ammation, making an individual more likely to engage in PA (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has posited that endogenous cannabinoids (i.e., cannabinoids occurring naturally in the body) provide a reward pathway for the addictive properties of PA, which may be disturbed by the consumption of exogenous cannabinoids (i.e., cannabis use), but this mechanism is not fully understood (17). Alternatively, it has been suggested that exogenous cannabinoids have indirect positive effects on health by reducing pain and in ammation, making an individual more likely to engage in PA (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Comparable to the aforementioned growing number of psychostimulants, synthetic cannabinoids have boomed considerably, irrespective of recent indications of possible nephrotoxic properties . Noteworthy, at least concerning the use of cannabis, more in‐depth knowledge regarding its effect on exercise and recovery was considered desirable especially in the light of modified political and legal regulations that recently came into effect and potentially affect a future anti‐doping case management . The need for capabilities to analytically cope with the enormous number of new synthetic cannabinoids has resulted in a variety of test methods of colorimetric, immunological, and mass spectrometric nature that have comprehensively been reviewed by several authors .…”
Section: Cannabinoids and Narcoticsmentioning
confidence: 99%
“…[206] Noteworthy, at least concerning the use of cannabis, more in-depth knowledge regarding its effect on exercise and recovery was considered desirable especially in the light of modified political and legal regulations that recently came into effect and potentially affect a future anti-doping case management. [207] The need for capabilities to analytically cope with the enormous number of new synthetic cannabinoids has resulted in a variety of test methods of colorimetric, immunological, and mass spectrometric nature that have comprehensively been reviewed by several authors. [208][209][210] Scheidweiler et al reported on the use of a nontargeted sequential windowed acquisition of all theoretical mass spectra (SWATH) approach, [211] allowing to successfully detect metabolites of 21 frequently identified synthetic cannabinoids [212] from human urine.…”
Section: Cannabinoids and Narcoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…New evidence is emerging that the euphoric effects experienced during exercise, also termed as “runner’s high,” may be the result of the actions of endogenous cannabinoid release during exercise rather than endorphins (10). The G-protein coupled cannabinoid 1 receptors (CB1) in the brain have been observed to be closely linked to opioid receptors, and the dopaminergic reward pathways suggesting endogenous cannabinoid release with PA could be a major reason why regular exercise is perceived as highly rewarding (11, 12).…”
Section: Introductionmentioning
confidence: 99%